Piety and commercialization da’wah: the influence of Hanan Attaki's Kajian on young urban muslims in Indonesia - Haq, Syamsul (Al-Misbah (Jurnal Islamic Studies), 2024)
Urban youth's growing piety and social media's expansion are intertwined, as shown by the resurgence of influential relocated people. Modern youngsters are disinterested in religious theology and prefer digital preachers who can answer their inquiries quickly. This has changed youth religion, which the media business has exacerbated. Thus, some renowned da'i, notably in Indonesia, use the internet to spread da'wah. Hanan Attaki, a famous preacher, often addresses youth issues on social media. Mental health, loneliness, future fear, and sin remorse are common concerns. This study aims to analyze piety and commercialization of da’wah which is Hanan Attaki’s case in kajian towards young urban Muslims in Indonesia. This research uses a qualitative case study method and literature review as an additional reference. Data collection using interview and documentation techniques such as journal articles, books, and information from the internet as secondary resources. The result of this study the success in commercializing Ustadz Hanan Attaki's influence preaching can be categorized as first, branding suitable for young people's da'i, second, specialization, such as his being an expertise in da’wa from his education journey, and third, building social contacts, which is a process where media and technology can penetrate geography such as social media or internet.